Berlioz in Time From Early Recognition to Lasting Renown - Bloom, Peter (Eastman Studies in Music, 2022)
Fourteen revealing essays by a prominent Berlioz authority on some of the composer's acclaimed compositions (the Symphonie fantastique, Les Nuits d'été, Les Troyens) and writings (the celebrated Mémoires). Written for both music lovers and scholars, these essays probe some of Berlioz's major works, including the Symphonie fantastique (the period of whose genesis is newly explored), Les Nuits d'été (whose origins are newly clarified by a revelation regarding Berlioz's possible muse), the Symphonie militaire (whose existence is examined in the period before it became the Symphonie funèbre et triomphale), Les Troyens (whose epilogue is seen as a paean to Napoléon III), and Béatrice et Bénédict (whose text reveals extraordinary understanding of the original play). The essays consider anew Berlioz's relationships with Franz Liszt (with whom the composer shared intimate details of his marriage to Harriet Smithson) and Richard Wagner (by whom the Frenchman was both charmed and alarmed), his travels in Germany (revealed as having had a specifically administrative purpose), his appreciation of English literature and Shakespeare (on whose work he was considered an expert), his modus operandi in composing the Mémoires, and his major twentieth-century biographers. Of conspicuous concern are the "politics" of a man sometimes erroneously viewed as distant from the political arena. This book is openly available in digital format, under Creative Commons license CC BY-NC-ND, thanks to generous funding from The New Berlioz Edition Trust.